2015
DOI: 10.2500/ajra.2015.29.4205
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Prostaglandin E2 Receptor Subtypes in Aspirin Tolerant Adult Chinese with Chronic Rhinosinusitis

Abstract: EP receptor expressions present different features in healthy subjects and patients with CRS. The upregulated EP1 receptor in eosinophilic CRSwNP might be associated with excessive infiltrations of eosinophils and other inflammatory cells. The accurate role of the four EP receptors in the pathogenesis of different CRS remains to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, the expression was lowest in aspirin-sensitive patients [198,199]. Moreover, increased EP1 receptor expression was associated with the eosinophilic phenotype in patients with nasal polyps without aspirin intolerance [194]. In a recent study, exposure to cigarette smoking was related with diminished expression of EP2 and EP4 receptors in nasal polyps of patients with chronic rhinosinusitis, which might explain the severe inflammation caused by smoking [200].…”
Section: Nasal Polypsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the expression was lowest in aspirin-sensitive patients [198,199]. Moreover, increased EP1 receptor expression was associated with the eosinophilic phenotype in patients with nasal polyps without aspirin intolerance [194]. In a recent study, exposure to cigarette smoking was related with diminished expression of EP2 and EP4 receptors in nasal polyps of patients with chronic rhinosinusitis, which might explain the severe inflammation caused by smoking [200].…”
Section: Nasal Polypsmentioning
confidence: 95%
“…Few studies have investigated PGs in nasal polyps, whereas comparatively more have assessed their roles in asthma or allergic rhinitis. However, the clinical relevance of PGs has been well demonstrated, even disregarding their association with aspirin sensitivity [194]. PGE 2 concentrations and COX-2 mRNA expression were lower in nasal polyp tissues than in nasal mucosas, either from healthy controls or from patients with chronic rhinosinusitis without nasal polyps.…”
Section: Nasal Polypsmentioning
confidence: 99%
“…ECRSwNP and NECRSwNP represent two distinct endotypes of CRSwNP that exhibit different clinical and pathologic features [18][19][20][21]. For better management of ECRSwNP and NECRSwNP, there is a clear need to investigate the underlying different molecular mechanisms of these two endotypes.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing EP receptors in CRS subtypes, Xie et al 1 found enhanced EP1 receptor messenger RNA (mRNA) and protein expression in eosinophilic CRS with nasal polyps (CRSwNP). However, EP4 mRNA levels were higher than EP1, EP2, and EP3 levels in controls; in CRS without nasal polyps (CRSsNP); and in noneosinophilic CRSwNP.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%
“…However, EP4 mRNA levels were higher than EP1, EP2, and EP3 levels in controls; in CRS without nasal polyps (CRSsNP); and in noneosinophilic CRSwNP. 1 Nasal tissue eosinophilia is a hallmark of CRSwNP, especially in patients from Western countries. Results of studies have shown an association between tissue eosinophilia and polyp recurrence.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%